The Urgency of Environmental Management From the Al Quran Perspective - Rusdiansyah Rusdiansyah; Rosalina Kumalawati; Muhammad Efendi (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Al-Qur'an is a holy book that does not only discuss religious issues but all dimensions of life including environmental issues. The environmental damage around us needs serious attention. One of the environmental damage causes is the lack of practice of religious values. Therefore, the role of religion in providing solutions to environmental problems is very much needed. Based on this, Â it is very important to do research with the title â€œThe Urgency of Environmental Management from the Al Quâ€™ran Perspectiveâ€. The research method is descriptive qualitative by explaining the concept of environmental management from the perspective of the Qur'an. The collection of data needed for this research is secondary data using Library Research (Library Studies). The approach in this study uses the approach of the science of interpretation (tafsir madhu'iy) and the science of geography because it is related to the study of the Qur'an and the environment. The result of this study indicates that the environmental elements specifically and in detail are mentioned in the Qurâ€™an. Environmental problems that often occur in our lives are related to these elements, such as al-ardh (earth), as-sama (atmosphere), al-mÃ¢ (water), anhÃ¢r (river), jabÃ¢l/jibÃ¢l (mountain), etc. The Qur'an also mentions mujmal (generally) environmental damage as a result of the actions of human hands. The damage occurred through the human hand, so it is through human hands to fix it for the sake of realizing sustainable environmental development.